Study on Behaviour of Cellular Concrete Slab - Nachiar S, Sindhu; S, Anandh; veerarajan, Jeyem (International Journal of Engineering and Technology, 2018)
Generally for any construction, normal conventional concrete is used to obtain required strength as per design. In the construction industry, now a day’s many construction techniques are in practice to minimise the self weight of concrete, thereby reducing the size of structural elements. One of the most widely adopting techniques is use of light weight concrete. But use of these light weight concrete do not fulfil the strength requirement as per the design of the structure. Hence it is used only as non-load bearing structural elements in the field. In view of this, in this study the attempt has been made to introduce the air voids in conventional concrete without compromising the strength. In this work the air voids are introduced in the concrete slabs and it is tested in the laboratory to know the performance. For this purpose, the slab of the size of 600mm x 600mm x 100mm is prepared with the voids of diameters 30mm, 35mm and 40mm. The voids are introduced in the concrete slab in four different configurations (line, X, I and matrix) to prepare the cellular elements. The normal and cellular slabs are tested under single point loading and the effect of various configurations is studied at the age of 28 days. From the test results, it was found that the slab with void volume of 1.59% shows the lowest stiffness and the slab with void volume of 2.28% shows the highest stiffness.